1997
DOI: 10.1152/jn.1997.77.5.2385
|View full text |Cite
|
Sign up to set email alerts
|

Two-Tone Distortion on the Basilar Membrane of the Chinchilla Cochlea

Abstract: Basilar membrane responses to pairs of tones were measured, with the use of a laser velocimeter, in the basal turn of the cochlea in anesthetized chinchillas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
103
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 62 publications
(91 reference statements)
12
103
0
Order By: Relevance
“…In these instances, the iDP generally increased in level as the f 2 /f 1 ratio decreased, which was similar to observations for the noninvasive measures of the 2f 1 -f 2 iDPs in Figure 2. Some of the clearest examples analogous to the present methods can be seen in Figures 6 and 7 of Robles et al (1997). Similar f 2 /f 1 ratio functions were also obtained by Rhode (2007), even when the CF of the BM site was at f 2 , i.e., near the iDP site of generation.…”
Section: Validity Of Noninvasive Techniquesupporting
confidence: 86%
See 2 more Smart Citations
“…In these instances, the iDP generally increased in level as the f 2 /f 1 ratio decreased, which was similar to observations for the noninvasive measures of the 2f 1 -f 2 iDPs in Figure 2. Some of the clearest examples analogous to the present methods can be seen in Figures 6 and 7 of Robles et al (1997). Similar f 2 /f 1 ratio functions were also obtained by Rhode (2007), even when the CF of the BM site was at f 2 , i.e., near the iDP site of generation.…”
Section: Validity Of Noninvasive Techniquesupporting
confidence: 86%
“…For example, as the f 2 /f 1 ratio is decreased, the 2f 1 -f 2 DPOAE from the ear canal often increases to a maximum at an Boptimal^f 2 /f 1 ratio of 1.2-1.25 and then dramatically decreases at narrower f 2 /f 1 ratios (Harris et al 1989;Johnson et al 2006). This results in the well-described inverted U-shaped f 2 /f 1 ratio function for DPOAEs (e.g., Harris et al 1989), which is often not observed in similar functions obtained for iDPs measured directly on the BM (e.g., Cooper and Rhode 1997;Rhode and Cooper 1997;Robles et al 1997) when the iDP is located at the characteristic frequency (CF) of the measurement site. That is, the 2f 1 -f 2 DP on the BM continues to increase in level as the f 2 /f 1 ratio decreases toward 1.0.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As one of various cochlear nonlinearities, distortion products (DPs) are a response to an absent tone after a two-tone pair is transmitted to the hearing apparatus. This phenomenon was observed 50 years ago in the auditory nerve [2], in otoacoustic emissions [3], and on the basilar membrane (BM) [4,5]. Also, the amplitudes of DPs depend on the sound pressure levels of the two-tone pairs, and show a pattern of maximum values being distributed on a positive linear path and gradually decreasing when the difference in the two-tone pair level is increased [6,7].…”
Section: Introductionmentioning
confidence: 86%
“…Note that for the 62-dB SPL masker level, gray symbols fall below the line indicating where d′ equal 1, but the open symbols fall above this line. The amplitudes of cochlear distortion products are below the amplitudes of the primary frequencies (Goldstein 1967;Buunen and Rhode 1978;Dolan 1990, 1993;Robles et al 1997;Cooper and Rhode 1997). Since the levels of the primaries for the 500-Hz F0 tone complex were 60-dB SPL, then the distortion product at 500 Hz should have been below 60-dB SPL.…”
Section: Experiments 1: Effect Of Low-pass Masking Noise On Behavioralmentioning
confidence: 94%